VIOLATIONS OF REGULATIONS BANNING TOBACCO ADVERTISING, PROMOTION AND DISPLAY IN VIETNAM AFTER THE IMPLEMENTATION OF THE LAW ON PREVENTION AND CONTROL OF TOBACCO HARMS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe evidence on the current situation of violations of regulations banning tobacco advertising, promotion, sponsorship and display, and to examine the level of exposure to, and emerging forms of, tobacco marketing in Vietnam after the Law on Prevention and Control of Tobacco Harms came into effect.Methods: A review study was conducted by examining research and publications released between 2013 and 2024 that addressed violations of tobacco TAPS ban regulations and population exposure to TAPS activities in Vietnam. This review was combined with a systematic analysis of relevant legal and regulatory documents.Results: Violations of tobacco TAPS bans remain widespread at tobacco retail points. The proportion of retail outlets violating tobacco advertising regulations ranged from approximately 40% to 70%, and more than 80% of outlets were found to have violated display quantity regulations, depending on location and survey period. The tobacco industry has increasingly exploited new marketing channels, such as social media and product trial events, to promote tobacco products, particularly targeting young people.Conclusion: It is necessary to strengthen strict enforcement of existing tobacco TAPS ban regulations at points of sale, expand regulatory oversight of new tobacco products, and intensify communication and monitoring efforts to reduce population exposure—especially among adolescents and young people.
Keywords: Law on Prevention and Control of Tobacco Harms; tobacco advertising; tobacco promotion; tobacco sponsorship; violations; point of sale